Some Results of (Î±, Î²) Derivations on Prime Semirings - Rasheed, Maryam K.; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2019)
This paper investigates the concept (Î±, Î²) derivation on semiring and extend a few results of this map on prime semiring. We establish the commutativity of prime semiring and investigate when (Î±, Î²) derivation becomes zero.